What Is the Best Proximal Anastomosis for the Free Right Internal Thoracic Artery during Bilateral Internal Thoracic Artery Revascularization? A Prospective, Randomized Study - S. Neragi-Miandoab; R. E. Michler; F. Lalezarzadeh; R. Bello; J. J. DeRose (Cardiology Research and Practice)
Objective. Bilateral internal thoracic artery (BITA) grafting provides improved graft patency and potential survival advantage in selected patients as compared to single left internal thoracic artery (LITA) revascularization. The ideal functional BITA configuration remains controversial. Methods. Patients undergoing planned BITA revascularization with greater than 75% stenosis in both the left anterior descending artery (LAD) and in a circumflex branch were prospectively randomized to one of two proximal free right internal thoracic artery (RITA) connections directly off the aorta (Ao) (n=12) or as a “t” graft off the LITA (t) (n=12). The LITA was placed to the LAD in all cases, and the RITA was placed to a single lateral wall vessel. Intraoperative transit time flow measurements of all arterial grafts were performed, and RITA fractional flow parameters were compared between the 2 groups. Results. There were no differences in preoperative patient variables between the two groups. Cross-clamp times (91.5+15.3 versus 68.0+12.5 minutes, P<0.01) and total cardiopulmonary bypass times (109.0+16.2 versus 85.0+15.1 minutes, P<0.01) were shorter in the t group. The Ao group demonstrated significantly higher mean RITA flow (38.3±13.5 versus 22.1±9.5, P<0.01), mean RITA conductance (flow/mean arterial pressure) (0.45±0.16 versus 0.28±0.11, P<0.01), RITA fractional flow (0.52 ± 0.15 versus 0.36 ± 0.11, P<0.01), and RITA fractional conductance (0.51 ± 0.15 versus 0.36 ± 0.11, P<0.01) than the “t” grafted patients. Thirty-day mortality and wound infection were 0% for each group. Over an average of 42.8+6.6 months of followup there were no mortalities in either group. Repeat angiography were performed in 4 patients (33%) in the Ao group and 2 patients in the t group (16%). One occluded RITA graft and one ostial RITA stenosis were detected in the Ao group. Conclusions. Acute flow measurements indicate that the free RITA anastomosed to the aorta provides more acute fractional RITA flow than composite “t” grafting to the LITA. Longer-term angiographic and clinical followup are necessary to determine the consequences of these acute hemodynamic findings.